An Analysis of the Concept of Dalālah Al-Mafhūm Al-Muwāfaqah in Usul Fiqh and Its Implications for the Establishment of Islamic Law - Nur Aidah Fauziah; Fatmawati Fatmawati; Zaenal Abidin (Penerbit Hellow Pustaka, 2025)
Dalalah al-mahfûm al-muwâfaqah is one of the methods of understanding texts in ushul fiqh which plays an important role in exploring the legal meaning of the syar'i text. This study aims to analyze the concept of mahfûm al-muwâfaqah, its basis in the syar'i text, and how it is implied in determining Islamic law. The methodology used is qualitative-descriptive with a normative analysis approach. The results of the study show that mahfûm al-muwâfaqah has strong legitimacy in the Qur'an and Sunnah, and is an important instrument in building legal analogies and ijtihad. The implications are very broad, especially in responding to modern legal problems that are not explicitly mentioned in the text.